Pengembangan Video Animasi Berbasis Permainan Edukatif untuk Meningkatkan Keterampilan Gerak Dasar Siswa di SDN 8 Dauh Puri - Agus Nuarta; Aris Fajar Pambudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop learning media in the form of an animated video based on educational games to improve the fundamental movement skills of first-grade elementary school students. This study uses a Research and Development (R&D) approach based on the ADDIE model: analysis, design, development, implementation, and evaluation. The subjects of the study were 60 first-grade students at SDN 8 Dauh Puri, selected using simple random sampling and divided into a control group and an experimental group. Data collection techniques included interviews, observations, questionnaires, tests (pre-test and post-test), and documentation. Data were analyzed using qualitative and quantitative approaches, including descriptive analysis and a paired-sample t-test. The results showed that the animated video product based on educational games had a very high level of validity, as assessed by material experts (93%), media experts (86%), and language experts (90%). The implementation results also showed a significant increase in students' basic motor skills, with the average pre-test score of 58.55 rising to 82.02 on the post-test. The paired-sample t-test results showed a significant difference (p < 0.05) with a very large effect size. Furthermore, the practicality test achieved a 90% success rate, indicating the media's ease of use in the learning process. These results have implications for integrating innovative technology as a learning medium in physical education classes, especially in elementary schools. Keywords: Animated Video, Fundamental Movement, Game